2023
DOI: 10.24875/gmm.m19000301
|View full text |Cite
|
Sign up to set email alerts
|

Pneumocystis jirovecii detection and genotyping from HIV-positive and HIV-negative Mexican patient samples

Abstract: Introduction: Pneumocystis jirovecii is an atypical fungus particularly detected in HIV-positive or transplanted patients. Objective: To detect and genotype Pneumocystis jirovecii in patient samples from two hospitals in Mexico City. Method: Eighty-nine respiratory tract samples, corresponding to 53 patients (30 HIV-positive and 23 HIV-negative) with respiratory symptoms and to 11 healthy individuals included as negative control, were processed. DNA was extracted and amplified by nested polymerase chain reacti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…Five studies were conducted from the USA [ 50 52 , 68 , 73 ]; three studies, each were conducted in South Africa [ 67 , 72 , 90 ], Japan [ 81 , 84 , 85 ], and Thailand [ 61 , 78 , 86 ]; two studies, each were conducted in Iran [ 75 , 80 ], France [ 45 , 66 ], and Mexico [ 40 , 47 ]; one study each was conducted in Ethiopia [ 39 ], Tanzania [ 60 ], Malawi [ 57 ], Spain [ 38 ], Cameroon [ 76 ], India [ 54 ], Taiwan [ 89 ], Zambia [ 79 ], and a study was from five European countries (France, Austria, Belgium, Croatia, Germany) [ 70 ].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Five studies were conducted from the USA [ 50 52 , 68 , 73 ]; three studies, each were conducted in South Africa [ 67 , 72 , 90 ], Japan [ 81 , 84 , 85 ], and Thailand [ 61 , 78 , 86 ]; two studies, each were conducted in Iran [ 75 , 80 ], France [ 45 , 66 ], and Mexico [ 40 , 47 ]; one study each was conducted in Ethiopia [ 39 ], Tanzania [ 60 ], Malawi [ 57 ], Spain [ 38 ], Cameroon [ 76 ], India [ 54 ], Taiwan [ 89 ], Zambia [ 79 ], and a study was from five European countries (France, Austria, Belgium, Croatia, Germany) [ 70 ].…”
Section: Resultsmentioning
confidence: 99%
“…Our random-effects model showed that in twenty-nine eligible studies [ 38 40 , 45 , 47 , 50 52 , 54 , 57 , 60 , 61 , 66 68 , 70 , 72 , 73 , 75 , 76 , 78 81 , 84 86 , 89 , 90 ], the pooled prevalence of HAP was 35.4% (95% CI:23.8 to 47.9; I 2 : 99.4%) ( Table 2 ). There is a negligible publication bias between studies (intercept: 6.946; 95% CI:-24.750 to 38.642; P = 0.6566).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations